Introduction of a new type of anti-clog suction tube and aspirator (介绍一种新型防堵塞吸引管及吸引器) - LI Minglan (李明兰); YANG Hui (杨晖); TANG Wenqin (唐文琴) (中西医结合护理)
T his paper introduced a new type of anti-clog suction tube and aspirator. This new type anti-blocking suction tube was designed to collect the sample of tissue in good condition and reduce the incidence of prolonged operation time cased by blockage and sample loss. (设计一种防堵塞效果更好且能够收集较为完好的组织标本的防堵塞吸引管, 避免因吸引管堵塞引起的手术时间延长和标本的遗失。)